2020
DOI: 10.2308/issues-19-060
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Effective Tax Rates Using Data Analytics

Abstract: Tomorrow's accounting professionals need to understand both accounting and data analytics. To meet these needs, we developed a case that combines an important area of tax accounting, Effective Tax Rates (ETRs), with multiple data analysis skills. The case can be completed in Excel, or with Tableau and/or Alteryx, using Compustat or public data. The case's learning objectives for students are to: (1) expand knowledge of data analytics and ETRs; (2) use critical-thinking skills to identify economic, industry, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Numerous studies have consistently demonstrated that the integration of data analytics skills into the study of taxation law may be effectively achieved through the utilization of Excel spreadsheets. This assertion is supported by the works of Laptante and Vernon (2021), Alarie, Niblett, and Yoon (2021), Cheng (2021), andSledgianowski, Petra, Palaez, andZhu (2021). The students utilised Microsoft Excel to successfully accomplish the tax workpapers, compute tax rates and income, conduct data analysis and visualization, and gain access to pertinent databases.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Numerous studies have consistently demonstrated that the integration of data analytics skills into the study of taxation law may be effectively achieved through the utilization of Excel spreadsheets. This assertion is supported by the works of Laptante and Vernon (2021), Alarie, Niblett, and Yoon (2021), Cheng (2021), andSledgianowski, Petra, Palaez, andZhu (2021). The students utilised Microsoft Excel to successfully accomplish the tax workpapers, compute tax rates and income, conduct data analysis and visualization, and gain access to pertinent databases.…”
mentioning
confidence: 80%
“…Furthermore, the use of digital platforms in education can efficiently assist students in recognizing and comprehending legal regulations (Franklin et al, 2020). According to Cheng, Shaw, and Yurko (2021), it is recommended that data analytics be included in the curriculum to acquaint students with the methodologies employed in tax data analysis. Hence, a methodology based on fundamental concepts, such as the 'extract, transform, and load' (ETL) technique employed by novice accounting practitioners, can be included into the educational environment.…”
Section: Integrating Data Analytics Proficiency In Taxation Law Educa...mentioning
confidence: 99%
“…As with efforts focused on BA programs, discipline‐driven efforts also saw educators put forth examples of instructional content, many of which examined projects rather than entire courses (e.g., Cainas et al., 2021; Cheng et al., 2021; Haywood & Mishra, 2019; Hoelsher & Mortimer, 2018; Kroes et al, 2013; Lim & Heinrichs, 2021; Roethlein et al., 2021). In fact, the emphasis on using real‐world projects is a recurrent theme throughout BA program literature (e.g., Chen et al., 2016; Nestorov et al, 2019; Riordan et al., 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…No CDO também estão incluídas as estratégias de ensino utilizadas pelos professores. A esse respeito, pesquisas têm testado múltiplas técnicas pedagógicas visando aumentar a performance discente, tais como jogos e gamificação (Beatson et al, 2020;ElKelish & Ahmed, 2021;Kuang, Adler, & Pandey, 2021), tecnologia (Francescucci, Kellershohn, & Pyle, 2021;Namin, Ketron, Kaltcheva, & Winsor, 2021), estudo de caso instrucional (Cheng, Sapkota, & Yurko, 2021), narrativas (Grimm, 2021;Taylor, Marrone, Tayar, & Mueller, 2017), tipo, frequência e políticas de avaliação (Miglietti, 2021;Nakos & Whiting, 2018;Nsor-Ambala, 2020) e assim por diante. No caso do grupo IES, o propósito é verificar como variáveis das instituições de ensino estão associadas ao desempenho acadêmico.…”
Section: Performance Discente E Grupos CDI Cdo E Iesunclassified